POLA BAHASA GENERASI Z DI LINGKUNGAN UNIVERSITAS TADULAKO - Wulandari Wulandari; Asrianti Asrianti (Universitas Muhammadiyah Surabaya, 2025)
This study aims to describe the linguistic patterns of Generation Z within the academic environment of Tadulako University. The term